2020
DOI: 10.1155/2020/1820978
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Lingual Frenulum: Histological Structure, Tissue Composition, and Implications for Tongue Tie Surgery

Abstract: Lingual frenotomy has become an increasingly common surgical procedure, performed for a broad range of indications from birth through adulthood. This study utilizes histology to define the structure and tissue composition of the lingual frenulum and floor of mouth (FOM) fascia. En bloc specimens of anterior tongue, lingual frenulum, and FOM tissues were harvested from ten embalmed adult cadavers. An additional three fresh tissue cadaveric specimens were frozen with the tongue supported in an elevated position,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
10
0
4
Order By: Relevance
“…Recently, the anatomical details of tongue muscles have been appreciated by the development of the super-resolution volume reconstruction method ( Woo et al, 2012 ), establishment of a spatial-temporal atlas during speech and swallowing ( Woo et al, 2015 ) and the segmented analysis of different muscle fibers on MRI imaging ( Stone et al, 2018 ). Furthermore, the increase of fat depositing in the tongue base of obese and aging patients ( Kim et al, 2014 ), regional differences in proportion and diameter of muscle fiber types ( Stål et al, 2003 ) as well as the size and collagen composition of the lingual frenulum ( Guilleminault et al, 2016 ; Mills et al, 2020 ) would be related to the stiffness measurement in patients with OSA. In addition, we found that the age distribution of the participants in their study ( Chang et al, 2020 ) was different from that of ours.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the anatomical details of tongue muscles have been appreciated by the development of the super-resolution volume reconstruction method ( Woo et al, 2012 ), establishment of a spatial-temporal atlas during speech and swallowing ( Woo et al, 2015 ) and the segmented analysis of different muscle fibers on MRI imaging ( Stone et al, 2018 ). Furthermore, the increase of fat depositing in the tongue base of obese and aging patients ( Kim et al, 2014 ), regional differences in proportion and diameter of muscle fiber types ( Stål et al, 2003 ) as well as the size and collagen composition of the lingual frenulum ( Guilleminault et al, 2016 ; Mills et al, 2020 ) would be related to the stiffness measurement in patients with OSA. In addition, we found that the age distribution of the participants in their study ( Chang et al, 2020 ) was different from that of ours.…”
Section: Discussionmentioning
confidence: 99%
“…PŮVODNÍ PRÁCE Linguální frenulum je při narození obvykle prodlouženo a dosahuje až k apexu. Poté ustupuje v důsledku růstu během prvních šesti měsíců a tento proces pokračuje až do šesti let života [11].…”
Section: Abstract: Dentistry Tongue-tie Ankyloglossia Anatomy Histolo...unclassified
“…More recently cases of tongue tie have appeared with increased frequency, most likely driven by the increased diagnosis of posterior tongue tie. However, the subsequent increase in frenotomy [ 106 ] have raised concerns about increased post-surgical complications [ 107 ]. Furthermore, preliminary evidence suggests that milk production can remain compromised in a number of infants after frenotomy for posterior tongue tie, indicating other potential causes of insufficient supply [ 108 ].…”
Section: Factors Impacting Milk Removalmentioning
confidence: 99%
“…Finally, the frenulum contains Type III collagen fibres which are much more distensible and mobile than the stronger less distensible Type I fibres previously identified [ 109 , 160 ]. Combined, these findings call for tongue tie grading to embrace normal variability and sheds light on concerns of adverse effects of frenotomy providing the basis for more prospective studies [ 107 ].…”
Section: Ankyloglossiamentioning
confidence: 99%